Negligible Effect of Estrogen Deficiency on Development of Skeletal Changes Induced by Type 1 Diabetes in Experimental Rat Models - Aleksandra Janas; Ewa Kruczek; Piotr Londzin; Sławomir Borymski; Zenon P. Czuba; Joanna Folwarczna (Hindawi Limited, 2020)
Although postmenopausal osteoporosis often occurs concurrently with diabetes, little is known about interactions between estrogen deficiency and hyperglycemia in the skeletal system. In the present study, the effects of estrogen deficiency on the development of biochemical, microstructural, and mechanical changes induced by streptozotocin-induced diabetes mellitus (DM) in the rat skeletal system were investigated. The experiments were carried out on nonovariectomized (NOVX) and ovariectomized (OVX) control and diabetic mature female Wistar rats. Serum levels of bone turnover markers (CTX-I and osteocalcin) and 23 cytokines, bone mass and mineralization, histomorphometric parameters, and mechanical properties of cancellous and compact bone were determined. The results were subjected to two-way ANOVA and principal component analysis (PCA). Estrogen deficiency induced osteoporotic changes, with increased bone resorption and formation, and worsening of microstructure (femoral metaphyseal BV/TV decreased by 13.0%) and mechanical properties of cancellous bone (the maximum load in the proximal tibial metaphysis decreased by 34.2%). DM in both the NOVX and OVX rats decreased bone mass, increased bone resorption and decreased bone formation, and worsened cancellous bone microarchitecture (for example, the femoral metaphyseal BV/TV decreased by 17.3% and 18.1%, respectively, in relation to the NOVX controls) and strength (the maximum load in the proximal tibial metaphysis decreased by 35.4% and 48.1%, respectively, in relation to the NOVX controls). Only in the diabetic rats, profound increases in some cytokine levels were noted. In conclusion, the changes induced by DM in female rats were only slightly intensified by estrogen deficiency. Despite similar effects on bone microstructure and strength, the influence of DM on the skeletal system was based on more profound systemic homeostasis changes than those induced by estrogen deficiency.